(3cJGH GHdhfjhS aj bWY GdNWhW Ydi GdfSHs - (3GHdhfjhSs
(3ChdgG (B:s
(3EPG cGf NWjf ehVhYGf ai JSWM hgeG ZjQ eJfGgjf hcGf eJhGRjjf Ch eJbGWYjf hjYde Ydi cd hGMO efgeG fbWI s
(3BNQgG (B:s
(3hai GdhbhY GdQGHYI GdfSHI GdYXei abO jecfG Cf JNQL ef fbWI g` NWkG JbWY K Edi J ajchf GdNW GdeNQL CeG ai GdhbhY GdKGdK aeQ ajeG Hjf fbWJjf g` S s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cJHJ GdYfGhjf HNW chais
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1450s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs